Multistimuli Responsive Liquid‐Release in Dynamic Polymer Coatings for Controlling Surface Slipperiness and Optical Performance. Issue 20 (4th September 2019) - Zhao, Huaixia; Prieto‐López, Lizbeth Ofelia; Zhou, Xiaozhuang; Deng, Xu; Cui, Jiaxi
Abstract: Controllable stabilization of liquids on interfaces is emerging as a novel method to mediate surface properties. Here, the fast, stimuli‐responsive liquid release from dynamic polymer coatings is described to mediate surface slipperiness and optical performance. These polymer coatings consist of a slippery liquid‐locked rough surface and a liquid‐supplied bottom layer storing the liquid in embedded droplets. They are prepared by a simple one‐pot casting of a solution of cross‐linkable polymer and silicone oil in tetrahydrofuran. It is demonstrated that upon mechano‐, solvent‐, or thermo‐stimulation, the liquid stored in the bottom layer is released altering both surface slipperiness and optical properties of the coatings. Abstract : Multistimuli responsive liquid release for mediating surface slipperiness and optical performance is explored in a dynamic polymer coating, which consists of a slippery liquid‐locked rough surface and a liquid‐supplied bottom layer. Mechano‐, solvent‐, and thermo‐stimuli are demonstrated to trigger the release of liquid stored in the bottom layer altering both surface slipperiness and optical properties of the coatings.